2020
DOI: 10.1101/2020.08.10.238428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell Programmed Nutrient Partitioning in the Tumor Microenvironment

Abstract: The tumor microenvironment (TME) includes transformed cancer and infiltrating immune cells. Cancer cells can consume large quantities of glucose through Warburg metabolism that can be visualized with positron emission tomography (PET). While infiltrating immune cells also rely on glucose, disruptions to metabolism can contribute to tumor immunological evasion. How immune cell metabolism is programmed or restrained by competition with cancer cells for nutrients, remains uncertain. Here we used PET tracers to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…There were significant differences in the scores of 17 immune function gene sets between the two clusters. A recent study (34) has reported that it is not the cancer cells that consume a considerable amount of glucose. The researchers used 18F-FDG-PET to detect glucose consumption in mouse tumor models to quantify glucose intake by different cell populations in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences in the scores of 17 immune function gene sets between the two clusters. A recent study (34) has reported that it is not the cancer cells that consume a considerable amount of glucose. The researchers used 18F-FDG-PET to detect glucose consumption in mouse tumor models to quantify glucose intake by different cell populations in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that, in TME, competition for nutrients between cancer cells and T cells contributes to immunosuppression ( 45 , 46 ). Moreover, a recent study evaluated metabolic features of tumor cell types in vivo and revealed that individual cell populations had distinct programs of nutrient uptake that might serve an important role in the development of future cancer therapies by altering TME ( 47 ). In addition, we, also, observed markedly elevated expression of cell cycle- and DNA repair- (mismatch repair and nucleotide excision repair) related genes in the high ICI score group.…”
Section: Discussionmentioning
confidence: 99%
“…The TME imposes metabolic challenges to the functions of T cells and other immune cells that directly impact antitumor immunity and tumor progression. As cancer and myeloid cells employ aerobic glycolysis to support biosynthetic requirements for proliferation via the Warburg effect, they rapidly uptake glucose, glutamine, and amino acids, depleting the TME of these nutrients (DeBerardinis and Chandel, 2016; Ghoshdastider et al, 2021; Pavlova and Thompson, 2016; Reinfeld et al, 2021); furthermore, the poor vasculature creates regions of hypoxia within the TME. As such, the hypoxic, acidic, nutrient-deplete TME impairs the ability of T CONV to sustain their functional activity.…”
Section: Discussionmentioning
confidence: 99%